Empirical Testing of Genuine Savings as an Indicator of Weak Sustainability: A Three-Country Analysis of Long-Run Trends - Hanley, N.; Oxley, Leslie; Greasley, D.; McLaughlin, E.; Blum, M. (2015)
© 2015 Springer Science+Business Media Dordrecht Genuine Savings has emerged as a widely-used indicator of sustainable development. This approach to conceptualising what sustainability is about has strong links to work published by Anil Markandya and colleagues over 20 years ago. In this paper, we use long-term data stretching back to 1870 to undertake empirical tests of the relationship between Genuine Savings (GS) and future well-being for three countries: Britain, the USA and Germany. Our tests are based on an underlying theoretical relationship between GS and changes in the present value of future consumption. Based on both single country and panel results, we find evidence supporting the existence of a cointegrating (long run equilibrium) relationship between GS and future well-being, and fail to reject the basic theoretical result on the relationship between these two macroeconomic variables. This provides some support for the GS measure of weak sustainability.